As tecnologias digitais na educação básica: um olhar sobre o uso pedagógico das TICs na escola estadual Joaquim Nabuco no município de Taipu/RN - Fonseca, Hélio (Universidade Federal Rural do Semi-Árido, 2020)
This research aims to reflect on the use of computers in the teaching and learning process, approaching the new Information and Communication Technologies and their usefulness as didactic-pedagogical tools in basic education and their importance for the development of students. The main objective was to analyze the insertion of technologies in the pedagogical practice of elementary school teachers at Joaquim Nabuco State School, in Taipu, in Rio Grande do Norte. Specifically, it was verified the perception of teachers about the use of ICTs in education as a way of dynamizing the teaching-learning process and how it occurs in the school context, in addition to observing the perception regarding the importance of the computer lab in the school's daily life. The research was descriptive and exploratory and adopted qualiquantitative approaches. The results showed that teachers believe that the use of digital technologies in the school diagnosis environment is fundamental to the teaching-learning process, but there are still some obstacles to their effective insertion, such as the lack of training and the infrastructure of schools. In addition, they also showed recognition of the importance of the computer lab in the school environment.
Monografia
Keywords: Diagnóstico escolar; Laboratório de Informática; Educação básica; TICs na educação; School diagnosis; Computer lab; Basic education; ICTs in education; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA